2020
DOI: 10.1155/2020/8810443
|View full text |Cite
|
Sign up to set email alerts
|

Progresses in Synthesis of Polycarboxylate Superplasticizer

Abstract: The prerequisite to synthesize PCE was to prepare new macromonomers with controlled molecular mass, adjustable hydrophilic-lipophilic groups, long-chain alkyl groups, and large terminal hydroxyl groups as well. Structural modifications in the molecular scale of polycarboxylate superplasticizer (PCE) would lead to changes in properties of dispersion and water retention as well as enhancement in the compatibility of Portland cement and so on. This paper reviewed recent developments from synthetic methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In this scenario, only steric hindrance can stand to explain the dispersion of the cement particles. A study that was performed on the zeta potential produced by polycarboxylate (PC) based SP and sulfonate-based plasticizers showed that the PC SP produced almost negligible zeta potential compared to the sulfonatebased SP [47]. Dispersion by steric hindrance observed in the PC SP is caused by the presence of neutral sidelong ether chains.…”
Section: Mechanism Of Action Of Superplasticizersmentioning
confidence: 99%
“…In this scenario, only steric hindrance can stand to explain the dispersion of the cement particles. A study that was performed on the zeta potential produced by polycarboxylate (PC) based SP and sulfonate-based plasticizers showed that the PC SP produced almost negligible zeta potential compared to the sulfonatebased SP [47]. Dispersion by steric hindrance observed in the PC SP is caused by the presence of neutral sidelong ether chains.…”
Section: Mechanism Of Action Of Superplasticizersmentioning
confidence: 99%
“…This additional energy helps meet the threshold required to catalyze the polymerization reaction, and the reactivity of the free radicals significantly promotes the polymerization of monomers . Due to climate change, polyacrylamide, polyacrylonitrile, and poly­(carboxylic acid) have been widely used on the market for waterproof building materials and concrete additives in recent years. This trend has spawned more research on azo initiators, driving new species of azos to be used in the field of polymer materials. However, azo initiators have caused thermal hazards in the production and storage processes, causing significant losses to personnel and property, highlighting the need for thermal hazard assessment of emerging azo initiators.…”
Section: Introductionmentioning
confidence: 99%
“…Their mechanism of action on cement slurries is due to the predominant steric effect [22]. Much research has been devoted to the creation of superplasticizers and hyperplasticizers based on polycarboxylates [23][24][25].…”
Section: Introductionmentioning
confidence: 99%